A personal perspective on Raghu Varadhan's role in the development of Stochastic Analysis. - Lyons, T (Oxford-Man Institute of Quantitative Finance, 2009)
Stochastic Analysis is an area of mathematics that, in a little over 60 years, has grown from almost nothing to a signicant eld. It has importance for its intrinsic interest and for its contributions to other foundational \pure" areas of mathematics, as well as for its contributions to the applications of mathematics. These applications seem to be on an enormous and expanding scale, spanning engineering and climate modelling. It is totally clear to those that work in Stochastic Analysis that Varadhan has shaped the subject in hugely signicant ways, both in his personal contributions|in the sense of direction he has given| and in the guidance he has provided to his many outstanding colleagues and students.